Emotional design of multimedia learning using background images with motivational cues. (10th June 2020) - Chung, Sungwon; Cheon, Jongpil
Abstract: Emotional design for multimedia learning can be implemented primarily using aesthetic design elements (e.g., color, shape and layout); however, we still have limited understanding on emotional design using content features visually depicting motivational cues. This study examines how valence and arousal of emotional learning content, generated by background images, in multimedia learning influenced learners' retention of factual knowledge and cognitive load, using a 2 (valence: positive, negative) × 2 (arousal: moderately low, moderately high) between‐subjects experiment. The results showed significant interaction effects, implying the positive effects of using moderately low arousing negative images on both recognition and cued‐recall test scores. Both scores were significantly lower when moderately high arousing negative images were used; however, they did not differ with increasing arousal of positive images. The emotional content did not influence germane and extraneous loads. Our findings emphasize the need for considering optimal levels of valence and arousal in emotional design. Lay Description: What is already known about this topic: Past emotion studies in multimedia learning primarily focused on the benefits of aesthetic design elements with instructional functions triggering learners' positive emotion. "Real" decorative elements in multimedia learning may be effective for learning indirectly by arousing interest and motivation. What this paper adds: Emotional design of multimedia learning triggering learners' negative emotion can be effective for cognitive learning performance (i.e., retention of the learned knowledge) in optimal levels of content arousal. The emotional learning content, generated by background images using motivational cues, did not influence learners' germane and extraneous cognitive loads. Implications for practice and/or policy: Our findings can provide useful information for effective emotional design, which is implemented by content features of the design, especially in microlearning, online learning or mobile learning in which visuals are frequently and increasingly used as an essential part for both attention and retention for a short span of time.